Quadruple Helix Model in Inspiring the Development of Telematics Creative Industries Community-Based (The Study of Phenomenology on Industrial Startup in Malang) - Adi, Dodot Sapto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The results of research on the model of the quadruple helix in creative industry development inspire the telematics on 2016-2017 in Malang, development is the study sponsored by the Department of Industry and Trade of the East Java province, focused over the planning evaluation of Supporting Facilities Planning Unit of Information Technology Technical Services (2016). This research is based on the phenomenon of the movement on creative industries telematics in Malang. The initial debate carried by the Ministry of Commerce of Republic Indonesia on 2008, by applying the synergi of triple helix involving Government-Academia-Business. After their processes towards in decade, change the paradigm become quadruple helix, by positioning the creative industries community telematics as the main agent. The community has a strong social capital, since it has a free position of structural dependence of any party. Problems of social change becomes their urgency, by revealing the existence of the creative community telematics, based on their ability to contribute to prevent social insecurity due to the increasingly competitive job opportunities as well as trying. This research using interpretive phenomenology based on subjective approach. Main activities conducting in-depth interviews and observations at 13 main informant. All of them are in 5 (five) a network of community-based industries, and serves as the foundation of the Agency the Creative Information Technology, East Java (JITC) Malang. As for the focus of the research on the view of the world, the efforts of the Association, the pattern of relationship and communication. Qualitative analysis of interactive used achieve efficiency through discussion in focused, while applying the validity through triangulation. The result of this research described as follows: (1) telematics creative community has strong commitment to control the sustainability of industrial telematics; (2) community was proved to be able to improve the innovation performance; and (3) established a new community through relationships and the intensity of the communication is done by involving financial institutions, distributors, employers' association, marketing and recruiting the new entrepreneur through internship programs.